Avaliação em modelos digitais da forma do arco maxilar em pacientes classe II tratados ortodonticamente - Meller, Cecilia Romero (2020)
The purpose of this study were to analyze in digital models the changes that occurred in the shape of the maxillary dental arches in Class II patients treated orthodontically. The sample consisted of 20 class II patients who were treated orthodontically. Patients were classified according to the growth pattern, for SN.GoGn ≤ 34º (Horizontal) and for SN.GoGn> 34º (Vertical). A total of 40 study models, 20 initial models (T0) and 20 final models (T1), were scanned (iTero Element; Align Technology, San Jose, CA, USA) and analyzed using the OrthoAnalyzer software (3Shape, Copenhagen, Denmark) . The paired t-test was used to compare the groups. There was a statistically significant increase in intercanine distance (p = 0.004) from T0 to T1. There was an increase in the angle formed between the midline and canines and second premolars, but with statistical significance only on the right side (LM - 13/15 = 3.17 degrees; p = 0.011) (LM - 23/25 = - 3.45 degrees; p = 0.086). There was no statistically significant difference in the intermolar distance (p> 0.05). Orthodontic treatment in class II patients caused a significant increase in intercanine distance as well as in the premolar region in the maxillary arch. There was no relationship between individuals with hypodivergent and hyperdivergent faces.